Immunogenicity and safety of the 13-valent pneumococcal conjugate vaccine in patients with immunocompromising conditions: a review of available evidence. Issue 11 (1st November 2020) - Chilson, Erica; Scott, Daniel A.; Schmoele-Thoma, Beate; Watson, Wendy; Moran, Mary M.; Isturiz, Raul
ABSTRACT: Immunocompromising conditions increase the risk of invasive pneumococcal disease (IPD). Vaccine uptake in patients with these conditions may be low in part because of concerns about decreased immunogenicity and safety in these high-risk groups. We conducted a literature search to identify publications describing antibody responses to 13-valent pneumococcal conjugate vaccine (PCV13) in immunocompromised individuals recommended for PCV13 vaccination by the US Advisory Committee on Immunization Practices (ACIP). This review summarizes immunogenicity data from 30 publications regarding the use of PCV13 comprising 2406 individuals considered at high risk for IPD by the ACIP. Although antibody responses to PCV13 in individuals with immunocompromising and high-risk conditions were variable and generally lower compared with healthy controls, the vaccine was immunogenic and was largely well tolerated. Based on these findings, concerns regarding immunogenicity and safety of PCV13 are not supported and should not be barriers to vaccination in high-risk populations.